GAMBARAN PERILAKU DAN PENGETAHUAN MAHASISWA KLUSTER KESEHATAN DAN SOSIO-HUMANIORA TERHADAP PENGOBATAN SENDIRI - , NERISA ARVIANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Self medication as the most widely used measures to treat minor ailments, must be accompanied by a qualified drug knowledge to support its success. This study was conducted to describe the behavior and knowledge of students in health cluster and students in socio-humanities clusters about self-medication. This study is a cross-sectional study, using a questionnaire that had been tested for validity and reliability as a means of collecting information from respondents. The sampling technique used was accidental sampling. The study involved 110 respondents from the health cluster and 116 respondents from sociohumanities cluster. Descriptive analysis is performed to describe the sociodemographic respondent, the respondent's behavior, and an overview knowledge of respondents to each question item. Analysis by chi-square test was conducted to determine whether there is a correlation between the cluster, gender, and class year of students to the level of knowledge about self medication. From the study, showed a mild disease that most often occurs in the student health cluster is fever (22.09%), while the cluster of socio-humanities students were headache (21.02%). The most commonly used drug in the second cluster is an analgesic-antipyretic with the percentage of 28.74% in health cluster and 43.71% in socio-humanities cluster. Where to obtain drugs at most is pharmacies with pesentase 55.28% in health clusters and 59.12% socio-humanities clusters. Source of information was the family, with the greatest percentage of 22.75% in the health cluster and 31.34% in the socio-humanities cluster. There are 70.91% of respondents Health Cluster included in good categories while the Socio- Humanities Cluster 20.69% of respondents are included in good categories. In the chi-square statistical test, showed that cluster, gender, and class affect the level of student knowledge about self-medication.